Synaptic transmission: Munc13 assembles onto PI(4,5)P 2 -rich domains into trimers that cooperate to capture vesicles - Feng Li; Abhijith Radhakrishnan; Sudhanshu Gautam; Gabriel Diaz; Ramalingam Venkat Kalyana Sundaram; Jeff Coleman; Hong Zheng; Kirill Grushin; Matthieu Chavent; James E. Rothman; Frederic Pincet (Proceedings of the National Academy of Sciences, 2026)
Munc13-1 is a key protein involved in priming synaptic vesicles for rapid release at the presynaptic plasma membrane. It was previously revealed that Munc13-1 cycles between at least two alternate conformations, an upright (open) molecular conformation organized as a trimer and a lateral (closed) conformation organized as a hexagon. Munc13 binds PI(4,5)P 2 , a plasma membrane phospholipid essential for vesicle docking and fusion. We report that Munc13 is recruited to PI(4,5)P 2 domains induced by a Syntaxin-1A juxta-membrane peptide in supported bilayers. Statistical analysis of the copy numbers of Munc13 within the domains suggests that Munc13 exists in clusters of three molecules, i.e., it assembles into trimers. The trimeric clusters disappear with engineered interface mutations disrupting the upright trimers in cryo-EM as well as reconstituted vesicle priming suggesting the trimers observed on bilayers are identical to the upright trimer structures. These upright trimers can also be identified by cryo-electron tomography on vesicles containing PI(4,5)P 2 and Syntaxin-1A. Clusters of 3 or more Munc13 trimers forming on PI(4,5)P 2 domains efficiently capture phosphatidylserine-containing small unilamellar vesicles via their C 2 C domains, as shown by the effect of mutations that disrupt synaptic vesicle binding in synapses. We propose a two-step model for vesicle priming: i) synaptic vesicles are captured by clusters of upright trimers of Munc13 that self-assemble within PI(4,5)P 2 enriched domains; ii) these trimers transition into lateral hexamers when vesicles have bound and the transition would be promoted when the closed conformation of Munc13 is stabilized by diacylglycerol binding, resulting from Ca 2+ -dependent hydrolysis of PI(4,5)P 2 .